2012
DOI: 10.1002/asna.201211686
|View full text |Cite
|
Sign up to set email alerts
|

Debris disks as seen by Herschel/DUNES

Abstract: The far-infrared excesses produced by debris disks are common features of stellar systems. These disks are thought to contain solids ranging from micron-sized dust to planetesimals. Naturally, their formation and evolution are linked to those of potential planets. With this motivation, the Herschel open time key programme DUNES (DUst around NEarby Stars) aims at further characterising known debris disks and discovering new ones in the regime explored by the Herschel space observatory. On the one hand, in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…They none-the-less offer symbiotic capabilities for imaging moderate contrast features in the bright regions of angularly small disks, enhanced when limited to polarized flux, in particular in the nIR where Strehl ratios and imaging performance is improved (and with spatial resolution, e.g., in K-band, comparable to STIS in the optical and thus providing, in combination, significant color diagnostics).In addition to the remainder of the approximately dozen HST-discovery images of debris disks not followed up in this study, including a few recently found in NICMOS LAPLACE reprocessed data withKLIP (Elodie et al 2014), there are now known debris disks at < 50 pc that are resolved at long wavelength by the Herschel Space Observatory. E.g., HD 139664 (reported in this paper with STIS), HD 127821 and HD 13337 all L IR /L star ~ 10 -4(Su et al 2013), HD 207129(Löhne et al 2012) and Eta Crv(Duchêne et al 2014). These Herschelresolved debris disks are typically too large in angular extent to image with extreme AO systems (and in some cases too large for complete imaging by the James Web Space Telescope (JWST)), but can be fully imaged with HST/STIS.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…They none-the-less offer symbiotic capabilities for imaging moderate contrast features in the bright regions of angularly small disks, enhanced when limited to polarized flux, in particular in the nIR where Strehl ratios and imaging performance is improved (and with spatial resolution, e.g., in K-band, comparable to STIS in the optical and thus providing, in combination, significant color diagnostics).In addition to the remainder of the approximately dozen HST-discovery images of debris disks not followed up in this study, including a few recently found in NICMOS LAPLACE reprocessed data withKLIP (Elodie et al 2014), there are now known debris disks at < 50 pc that are resolved at long wavelength by the Herschel Space Observatory. E.g., HD 139664 (reported in this paper with STIS), HD 127821 and HD 13337 all L IR /L star ~ 10 -4(Su et al 2013), HD 207129(Löhne et al 2012) and Eta Crv(Duchêne et al 2014). These Herschelresolved debris disks are typically too large in angular extent to image with extreme AO systems (and in some cases too large for complete imaging by the James Web Space Telescope (JWST)), but can be fully imaged with HST/STIS.…”
mentioning
confidence: 51%
“…reprocessed data withKLIP (Elodie et al 2014), there are now known debris disks at < 50 pc that are resolved at long wavelength by the Herschel Space Observatory. E.g., HD 139664 (reported in this paper with STIS), HD 127821 and HD 13337 all L IR /L star ~ 10 -4(Su et al 2013), HD 207129(Löhne et al 2012) and Eta Crv(Duchêne et al 2014). These Herschelresolved debris disks are typically too large in angular extent to image with extreme AO systems (and in some cases too large for complete imaging by the James Web Space Telescope (JWST)), but can be fully imaged with HST/STIS.…”
mentioning
confidence: 51%
“…The satellite Herschel overcome some of these difficulties, thanks to their greater sensivity and spatial resolution. Different Herschel surveys such as SUNS, DEBRIS (Matthews et al 2010;Phillips et al 2010), and DUNES (Eiroa et al 2010;Löhne et al 2012;Eiroa et al 2013) do include multiple systems in their samples. However, the circumstellar nature of the dust have been determined in few multiple systems (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For the massive, collisional disks we currently observe, only a small fraction of the dust spirals inward, such that the disk density interior to the ring is a much smaller fraction of the ring itself. However, theoretical studies suggest a much larger fraction of dust will spiral inward in less massive disks where collisions are rare, so much so that the disk can appear to be continuous all the way from the ring in to the sublimation distance when viewed at visible wavelengths (e.g., Wyatt 1999;Kuchner & Stark 2010;Löhne et al 2012;Kennedy & Piette 2015).…”
Section: Generate Disksmentioning
confidence: 99%